Patient perspectives of the climate of diversity, equity, and inclusion in the emergency department. Issue 5 (17th September 2022) - Davuluri, Kavya; Goyal, Nikhil; Gomez Acevedo, Harold; Folt, Jason; Jayaprakash, Namita; Slezak, Michelle; Caldwell, Martina T.
Abstract: Objective: Assessing the diversity, equity, and inclusion (DEI) climate of emergency departments (EDs) can inform organizational change to provide equitable, inclusive, and high‐quality care to their diverse patient populations. The purpose of this project was to investigate patient perspectives on the climate of DEI in an urban ED. Methods: This was a cross‐sectional survey study conducted in a large‐volume, urban ED in Detroit, MI, from November 2018 to January 2019. The survey was developed by an experienced ED DEI committee via an iterative process and broad consensus. Results: During their care in the ED, 849 patients completed an anonymous survey about their perspectives and experiences of DEI in that ED. Overall, the responses were favorable as most respondents reported that the ED staff treated patients from all races equally (75.8%) and made patients feel accepted (86%). However, some respondents felt that the ED staff's treatment of populations with greater complexity, such as patients who are mentally ill (16.8%) or lower income (14.3%), needs the most improvement. Conclusions: This DEI climate assessment survey of ED patients' perspectives revealed important insights that could guide strategic initiatives to advance DEI in the ED. This assessment may serve as a model for continuous evaluation of DEI over time and in multiple healthcare settings to help guide organizational change efforts.